2017
DOI: 10.1002/alr.22043
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary aspiration of sinus secretions in patients with cystic fibrosis

Abstract: This study provides direct evidence of aspiration of sinonasal secretions into the lungs of patients with CF and healthy adults in the recumbent position. The fact that both patients and controls aspirated secretions suggests that aspiration alone does not account for the pathogenesis of lung disease in CF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…6,9,11,[13][14][15][16] Furthermore, the unified airway hypothesis suggests that treating bacterial infection in the upper airway can also decrease bacterial burden in the lungs. [17][18][19] Since pulmonary infection is associated with increased mortality in lung transplant patients, ESS may improve clinical outcomes by decreasing the overall bacterial burden of the upper and lower airways. 20 However, the clinical impact of ESS on pulmonary status is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,11,[13][14][15][16] Furthermore, the unified airway hypothesis suggests that treating bacterial infection in the upper airway can also decrease bacterial burden in the lungs. [17][18][19] Since pulmonary infection is associated with increased mortality in lung transplant patients, ESS may improve clinical outcomes by decreasing the overall bacterial burden of the upper and lower airways. 20 However, the clinical impact of ESS on pulmonary status is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This case series discusses six patients who presented with pneumonitis‐related pulmonary symptoms caused by chronic cerebrospinal fluid fistulas and aspiration, a novel relationship that has not been previously discussed outside the author's first case report 16 . Although this is the first case series to report reversible chronic aspiration‐induced pneumonitis in the context of spontaneous skull‐base defects, previous studies show that sinonasal secretions aspiration can lead to aspiration pneumonitis 17,18 . We aim to underscore the importance of this potentially underdiagnosed entity, as the nonspecific presentation of headache with flu‐like symptoms in the setting of rhinorrhea often leads to a protracted diagnosis or in one of our patients surgical intervention for biopsy 1,5,9 .…”
Section: Discussionmentioning
confidence: 82%
“…CSF rhinorrhea can be considered as a cause of chronic pneumonitis despite the lack of direct evidence [ 8 ]. A controlled clinical trial has shown that sinonasal secretions can be transferred to the lungs whether in patients with cystic fibrosis or healthy subjects [ 9 ]. In this case, meningoencephalocele is located in the lateral wall of sphenoidal sinus and leads to persistent CSF rhinorrhea.…”
Section: Discussionmentioning
confidence: 99%